2018
DOI: 10.1002/2017jd027587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tropical‐Extratropical Interactions and Extreme Precipitation Events in the Middle East Based On Potential Vorticity and Moisture Transport

Abstract: Extreme precipitation events in the otherwise arid Middle East can cause flooding with dramatic socioeconomic impacts. Most of these events are associated with tropical‐extratropical interactions, whereby a stratospheric potential vorticity (PV) intrusion reaches deep into the subtropics and forces an incursion of high poleward vertically integrated water vapor transport (IVT) into the Middle East. This study presents an object‐based identification method for extreme precipitation events based on the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 118 publications
7
77
0
Order By: Relevance
“…We found that the composite of SLP during the negative phases of NAO and AO are characterized by positive SLP anomalies over Iceland, and negative SLP anomalies over the Azores High, for all seasons, except summer (which exhibit weaker anomalies). The negative phase of AO/NAO decreases the pressure gradient between the extra‐tropical and polar North Atlantic, resulting in a weakening of the Asian westerly jet stream over North Africa and the Middle East (de Vries et al ., ). This decreases the number of western disturbances, causing less precipitation and increasing the temperatures over the AP (Yadav et al ., ; de Vries et al ., ).…”
Section: Links Of Sat To Dominant Circulation Patternsmentioning
confidence: 97%
“…We found that the composite of SLP during the negative phases of NAO and AO are characterized by positive SLP anomalies over Iceland, and negative SLP anomalies over the Azores High, for all seasons, except summer (which exhibit weaker anomalies). The negative phase of AO/NAO decreases the pressure gradient between the extra‐tropical and polar North Atlantic, resulting in a weakening of the Asian westerly jet stream over North Africa and the Middle East (de Vries et al ., ). This decreases the number of western disturbances, causing less precipitation and increasing the temperatures over the AP (Yadav et al ., ; de Vries et al ., ).…”
Section: Links Of Sat To Dominant Circulation Patternsmentioning
confidence: 97%
“…The RST is a temporary extension of the African/Sudanese Low, characterized by a low-pressure tongue extending northward over the Red Sea toward the Eastern Mediterranean and its surroundings. The active RST (ARST) is linked to an intensified Arabian Anticyclone in the southeastern margin of the Arabian Peninsula, which enhances moisture transport from the Arabian Sea and the Gulf of Aden toward the Red Sea (e.g., Dasari et al, 2018;de Vries et al, 2016de Vries et al, , 2018. The RST systems are classified as nonactive, associated with hot and dry weather conditions, and active, associated with heavy precipitation and flash flooding in the Middle East (e.g., de Vries et al, 2013;Krichak et al, 2012;Shentsis et al, 2012;Tsvieli & Zangvil, 2005.…”
Section: Large-scale Slp Pattern During Westward Wind Eventsmentioning
confidence: 99%
“…The RST systems are classified as nonactive, associated with hot and dry weather conditions, and active, associated with heavy precipitation and flash flooding in the Middle East (e.g., de Vries et al, 2013;Krichak et al, 2012;Shentsis et al, 2012;Tsvieli & Zangvil, 2005. The active RST (ARST) is linked to an intensified Arabian Anticyclone in the southeastern margin of the Arabian Peninsula, which enhances moisture transport from the Arabian Sea and the Gulf of Aden toward the Red Sea (e.g., Dasari et al, 2018;de Vries et al, 2016de Vries et al, , 2018. Three significant differences in the SLP pattern exist when the winds are predominantly westward over the northern Red Sea in relation to the winter composite ( Figure 6).…”
Section: Large-scale Slp Pattern During Westward Wind Eventsmentioning
confidence: 99%
“…In the Middle East, an accurate estimation of precipitation variations over space and time is of importance for a variety of reasons and for numerous applications. First, the region represents one of the most arid regions in the world, where the impacts of climate changes on a wide range of natural and human environments (e.g., agriculture, water resources, food production, health, biodiversity) and even political influences (Burke et al ., ; Smith and Vivekananda, ) are likely to be exacerbated (Evans, ; de Vries et al ., ; ). As such, an accurate quantification of possible impacts necessitates a realistic representation of spatiotemporal characteristics of rainfall.…”
Section: Introductionmentioning
confidence: 99%